Implementing Character Education in Biology Learning to Foster Environmental Awareness Among High School Student of SMA Negeri 20 Medan - Rifda Rifda; Sayed Akhyar (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Character education is essential to achieving the Sustainable Development Goals (SDGs), particularly in shaping a principled and environmentally conscious generation. This study aims to describe the implementation of character education in biology lessons at SMA Negeri 20 Medan. Methodology: The method used is qualitative with a case study, involving biology teachers and 10th-grade students selected purposively. Data was collected through participant observation, semi-structured interviews, and documentation, then validated through triangulation of sources and methods. Findings: The results of the study indicate that character education is integrated through intraschool activities such as group prayers, laboratory experiments, discussions, and classroom cleanliness, and reinforced through extracurricular activities like Rohis. Teachers applied varied strategies, particularly Contextual Teaching and Learning (CTL), effectively fostering students' environmental awareness. The impact of implementation was evident in changes in students' attitudes, such as becoming more disciplined, responsible, and environmentally conscious. Contribution: These findings align with previous research on the effectiveness of contextual learning but contribute new insights by emphasizing the integration of intraschool and extracurricular activities as a simultaneous model for character education